2020
DOI: 10.3390/pathogens9010038
|View full text |Cite
|
Sign up to set email alerts
|

The Cell-Cycle Regulatory Protein p21CIP1/WAF1 Is Required for Cytolethal Distending Toxin (Cdt)-Induced Apoptosis

Abstract: The Aggregatibacter actinomycetemcomitans cytolethal distending toxin (Cdt) induces lymphocytes to undergo cell-cycle arrest and apoptosis; toxicity is dependent upon the active Cdt subunit, CdtB. We now demonstrate that p21CIP1/WAF1 is critical to Cdt-induced apoptosis. Cdt induces increases in the levels of p21CIP1/WAF1 in lymphoid cell lines, Jurkat and MyLa, and in primary human lymphocytes. These increases were dependent upon CdtB’s ability to function as a phosphatidylinositol (PI) 3,4,5-triphosphate (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…Intracellular levels of p21 CIP1/WAF1 are controlled transcriptionally, as well as post-translationally (Warfel and El-Deiry, 2013;Dutto et al, 2015). Previously, we demonstrated that p21 CIP1/WAF1 mRNA levels were not significantly altered in AaCdt-treated lymphocytes (Shenker et al, 2020); instead, we observed that the increases were likely dependent upon posttranslational modification as we have demonstrated a requisite role for the chaperone protein, HSP90 (Shenker et al, 2020). HSP90 has been shown to stabilize p21 CIP1/WAF1 and prevent proteasomal degradation (Jascur et al, 2005;Diehl et al, 2009).…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Intracellular levels of p21 CIP1/WAF1 are controlled transcriptionally, as well as post-translationally (Warfel and El-Deiry, 2013;Dutto et al, 2015). Previously, we demonstrated that p21 CIP1/WAF1 mRNA levels were not significantly altered in AaCdt-treated lymphocytes (Shenker et al, 2020); instead, we observed that the increases were likely dependent upon posttranslational modification as we have demonstrated a requisite role for the chaperone protein, HSP90 (Shenker et al, 2020). HSP90 has been shown to stabilize p21 CIP1/WAF1 and prevent proteasomal degradation (Jascur et al, 2005;Diehl et al, 2009).…”
Section: Resultsmentioning
confidence: 48%
“…Increased pH2AX has been interpreted by several investigators as not only an indicator of DDR activation, but also as a surrogate for Cdt-mediated DNA damage (Bezine et al, 2014;Frisan, 2016). It should be noted, however, that we previously demonstrated that AaCdt-mediated p21 CIP1/WAF1 upregulation in human lymphocytes is not linked to activation of the DDR; the doses of AaCdt required to induce cell cycle arrest (and apoptosis) do not induce increases of pH2AX (Shenker et al, 2006;Shenker et al, 2020). Therefore, we also evaluated the effect HdCdt and CjCdt at the doses employed in this study for their ability to induce increases in pH2AX in lymphocytes.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…We have proposed an alternative paradigm which is based upon our observation that CdtB, derived from A. actinomycetemcomitans aggregatibacter Cdt, is a potent PIP3 phosphatase; Cdt treated cells exhibit depletion of PIP3 and downstream PI-3K blockade: decreased phosphorylation of Akt (inactivation) and GSK3β (activation). Furthermore, we have demonstrated that CdtB toxicity, which we have observed in both proliferating cells and non-proliferating cells, is dependent upon its PIP3 phosphatase activity and not DNase activity (24,(62)(63)(64)(65). It is likely that the operative molecular mode of action relates to the amount of toxin employed, the bacterial source of Cdt and the host target cell.…”
Section: Discussionmentioning
confidence: 77%
“…As described above, the CDT is the other exotoxin produced by A. actinomycetemcomitans [ 2 ]. In their paper in the present Special Issue, Shenker and co-workers [ 12 ] report on the mechanism for CDT-induced apoptosis in T-lymphocytes. Their data demonstrate that toxin-induced apoptosis is dependent upon increased levels of specific intracellular signaling, and conclude that that the ability of CDT to impair lymphocyte proliferation and promote cell death therefore compromises the host response to CDT-producing organisms.…”
Section: Host–parasite Interactionsmentioning
confidence: 99%